Trophic structure of micronekton in the Northwest Pacific Ocean - Zhang, Jiaqi; Liu, Bilin; Hu, Song; Gong, Yi (Frontiers in Marine Science, 2022)
Stable isotope analysis has been widely used in the study of the trophic structure of marine micronekton in recent years. In this study, the carbon and nitrogen stable isotope values of fish, cephalopod, shrimp and zooplankton species were measured from samples collected in the Northwest Pacific Ocean in March and September 2019 to construct a continuous trophic spectrum and to compare isotope niches among species. In addition, we compared the variation of isotopic niches of micronekton among different groups and among different species, respectively. Significant differences of δ^13 C and δ^15 N values were detected among fish, cephalopod and shrimp groups with δ^13 C value ranges of ‒21.9‰ to ‒18.7‰, ‒21.3‰ to ‒17.7‰ and ‒20.4‰ to ‒19.5‰, respectively and the range of δ^15 N values was 7.0‰ to 12.4‰, 8.2‰ to 12.2‰ and 7.6‰ to 10.6‰, respectively. Using copepods as the baseline for estimating the average trophic level (TL) of micronekton, the TLs ranged from 2.67 to 4.80 and the average TLs for cephalopods, fishes and shrimp were 3.3 ± 0.3, 3.7 ± 0.6 and 4.0 ± 0.3, respectively. Myctophidae and Stomiidae occupied higher TLs. In addition, Oplophorus gracilirostris, Enoploteuthis chunii and Abralia similis had wide isotopic niches. Our results show that Myctophidae, Stomiidae, Oplophorus gracilirostris, Enoploteuthis chunii and Abralia similis play important roles in maintaining the stability of the Kuroshio-Oyashio ecosystem in the Northwest Pacific Ocean.